Study of the Properties and Mechanism of Action of "Bacillus velezensis" D-18 for Establishment as a Probiotic Bacterium in Aquaculture - Monzón-Atienza, Luis (2024)
Programa de Doctorado en Acuicultura Sostenible y Ecosistemas Marinos por la Universidad de Las Palmas de Gran Canaria Following an exhaustive sampling of wastewater from turbot aquaculture facilities in northern Spain, a meticulous screening process led to the isolation of a unique bacterium, subsequently identified as Bacillus velezensis D-18 through molecular sequencing. Drawing upon extensive literature supporting the genus Bacillus as beneficial microorganisms for the host, the probiotic potential of B. velezensis D-18 in the context of aquaculture was evaluated.